Characterization of an acidophilic α-amylase from Aspergillus niger RBP7 and study of catalytic potential in response to nutritionally important heterogeneous compound - Mukherjee, Riddha; Paul, Tanmay; Halder, Suman Kumar; Soren, Jyoti Prakash; Banerjee, Amrita; Mondal, Keshab Chandra; Pati, Bikash Ranjan; Mohapatra, Pradeep Kumar Das (Acta Biologica Szegediensis, 2018)
An acidophilic α-amylase from Aspergillus niger RBP7 was purified after solid state fermentation on potato peel substrate. Molecular mass of the purified α-amylase was 37.5 kDa and it exhibited 1.4 mg/ml and 0.992 μ/mol/min Km and Vmax values, respectively. The enzyme was stable in the pH range from 2.0 to 6.0, at high NaCl concentration (3 M) and at temperatures between 40 °C and 70 °C. The enzyme showed an optimal activity at pH 3.0 and at 45 °C. The enzyme was inhibited by Hg2+ and was stable in the presence of different surfactants (Tween 60, Tween 80, and SDS at 1% level) and different inhibitory reagents (β-mercaptoethanol, phenylmethylsulfonyl fluoride, and sodium azide). This acidophilic amylase enzyme can digest heterogeneous food materials, i.e. the mixture of rice, fish, bread and curry with comparable activity to the commercial diastase enzymes available.